Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1097/01.sap.0000101930.75241.55
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Musculoskeletal Symptoms Among Danish Women With Cosmetic Breast Implants

Abstract: We did not find an excess of rheumatic symptoms or symptom clusters among women with breast implants. In fact, the occurrence of mild, moderate, and severe musculoskeletal symptoms was generally lower among women with implants compared with women with other cosmetic surgery and women in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Gland Surg In contrast, the risk of Raynaud's phenomenon was not increased in five other smaller studies (10,12,(29)(30)(31).…”
Section: Ssc and Raynaud's Phenomenonmentioning
confidence: 85%
See 4 more Smart Citations
“…Gland Surg In contrast, the risk of Raynaud's phenomenon was not increased in five other smaller studies (10,12,(29)(30)(31).…”
Section: Ssc and Raynaud's Phenomenonmentioning
confidence: 85%
“…Two studies reported a 1.8 to 2.3-fold increase in risk of morning or joint stiffness among women with breast implants compared to women with other cosmetic surgeries or from the general population (15,29). Joint swelling was not more frequently reported (12,(27)(28)(29)31).…”
Section: Ra and Joint-related Symptomsmentioning
confidence: 98%
See 3 more Smart Citations